EFFECTIVENESS OF CORE STRENGTHENING ON LOW BACK PAIN IN DIASTASIS RECTUS ABDOMINUS - CHITRA; SURESHKUMAR, DR. SUGASRI (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
OBJECTIVES : To assess and decrease inter recti distance and intensity of pain in women with diastasis rectus abdominus. METHODS AND MATERIALS:Pretest and posttest experimental study design of 15 subjects with mean age from 35 to 55 years have a diastasis rectus abdominus and low back pain. This is used to find an inter recti distance by using digital caliper, they are participated in core strengthening program for 3 weeks. by focusing on core muscles activation with coordinated breathing. Inter recti distance and low back pain were assessed using digital caliper and visual analogue scale. RESULTS:The 3 week of core strengthening program significantly decreased in inter recti distance above and below umbilicus at rest. Decrease of inter recti distance and intensity of low back pain. CONCLUSION:After 3 weeks of intervention of core strengthening showed significant improvement on reducing pain intensity and inter recti distance. However, core strengthening was found to be more effective.